The Balto-Slavic question in the light of old Baltic borrowings in Finnic - Junttila, Santeri (Baltistica, 2016)
Most of the old Baltic borrowings in Finnic have been discovered through the East Baltic cognates of their loan original. Comparison material from Slavic is nevertheless much more relevant than it has been thought. This is confirmed by 20 Baltic loanwords in Finnic presented here. In eight cases, the original of the borrowing has cognates in Slavic but not in East or West Baltic. In the remaining twelve cases the meaning or the form of the original is not reconstructable without Slavic material. Thus these loan etymologies support the Baltic origin of Proto-Slavic.Middle Proto-Finnic received these borrowings during the last millennium B.C. from an extinct dialect phonologically close to Proto-Balto-Slavic.
Keywords: Balto-Slavic; Baltic Finnic; borrowings; loanwords; etymology